2011
DOI: 10.1186/1471-2458-11-53
|View full text |Cite
|
Sign up to set email alerts
|

Burden of disease in Thailand: changes in health gap between 1999 and 2004

Abstract: Background: Continuing comprehensive assessment of population health gap is essential for effective health planning. This paper assessed changes in the magnitude and pattern of disease burden in Thailand between 1999 and 2004. It further drew lessons learned from applying the global burden of disease (GBD) methods to the Thai context for other developing country settings.Methods: Multiple sources of mortality and morbidity data for both years were assessed and used to estimate Disability-Adjusted Life Years (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 20 publications
2
78
0
Order By: Relevance
“…Only a handful of countries have the capacity to generate their own national disease burden and cost-effectiveness estimates, including the United States, Mexico, Australia, New Zealand, Thailand, Singapore, and Japan. [26][27][28][29][30][31][32] High-income countries such as Australia and Japan have used their disease burden data to better prioritize health services delivery. 28,32 Latin American and African countries, such as Peru, Chile, Tanzania, and Botswana, have used burden of disease as a basis to construct a benefit package of essential and cost-effective interventions guaranteed to be provided to the entire population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a handful of countries have the capacity to generate their own national disease burden and cost-effectiveness estimates, including the United States, Mexico, Australia, New Zealand, Thailand, Singapore, and Japan. [26][27][28][29][30][31][32] High-income countries such as Australia and Japan have used their disease burden data to better prioritize health services delivery. 28,32 Latin American and African countries, such as Peru, Chile, Tanzania, and Botswana, have used burden of disease as a basis to construct a benefit package of essential and cost-effective interventions guaranteed to be provided to the entire population.…”
Section: Discussionmentioning
confidence: 99%
“…8 Earmarked sin taxes implemented in 2015 expanded PHIC fiscal space. 9 Accordingly, total benefit claims paid by PHIC has grown fourfold, from 30.5B PHP ($635.5M USD) in 2010 to 101.75B PHP ($2.11B USD) in 2016. 10 However, because PHIC and DOH have no explicit and systematic process by which diseases, conditions, and health interventions are prioritized, there is still great emphasis on expensive curative and inpatient care while coverage of costeffective interventions such as primary care services is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a study of multicountry data between 1980 and 2008 has shown a decreasing trend of mean blood pressure in western countries, but an increasing trend in south-east Asia and Oceania [3]. In Thailand, hypertension ranks third as a risk factor of burden of disease, and it is attributable to 600 000 DALY losses (6.6%) in Thai population each year [4]. Major complications of hypertension, such as stroke, are also among the most common DALY losses in the Thai population [4].…”
mentioning
confidence: 99%
“…Instead of that new methods are established to assess mortality statistics in developing countries (Bhattacharaya & Neogi, 2008). Currently, the popularity of studies evaluating AIDS-related mortality by means of verbal autopsy is increasing (Bundhamcharoen et al, 2011;Lopman et al, 2010;Negin et al, 2010). We believe that autopsy series represent most reliable sources in estimation of mortality trends.…”
Section: Resultsmentioning
confidence: 99%